Russia Coerces, but the Baltic States Persist: the Importance of Initiatives for Integration and Cooperation - Molis, Arūnas; Česnakas, Giedrius; Juozaitis, Justinas (Politologija, 2018)
[only abstract in English; full article, abstract in Lithuanian]The infrastructural dependency of the Baltic States on Russia, even a quarter of a century after the collapse of the Soviet Union, has lead to technological dependence and the maintenance of relations between scientists, business groups and political decision-makers. All this has further strengthened Moscow’s tools in the area of energy geopolitics in the Baltic region. On the other hand, use of the so-called “punishment” instruments, intended to force other states to review their policies toward a Moscow-leaning direction, has actually failed. Looking back, one may even say that the result was opposite: an aggressive Russian policy encouraged smaller countries to seek alternative supply routes, other partners and directions for integration. In this context, Lithuania may only appreciate that Moscow was not active enough in applying the positive instruments – offering preferential loans for the development of energy infrastructure, providing discounts for purchased resources etc. Namely these tactics would, in the long run, only increase the damage for Lithuania as an importer of energy resources. Thus, Russia’s pressure (primarily in the field of natural gas supply and pricing) did not force the Baltic States to act in accordance with its guidelines, for example, to refrain from criticizing the Nord Stream or postpone their integration into the network of Continental Europe. On the contrary – due to the lack of active application of negative measures and the absence of any positive instruments, Lithuania has invested in the LNG terminal, electricity interconnections, a synchronization project, and it took certain political measures by taking part in the creation of the EU Energy Union. Of course, some elements of the “punishment” policy have been successful for Russia: in 2009, the Ostrovets NPP project reduced the attractiveness of the joint Baltic States’ and Poland nuclear power plant project to the extent that it was abandoned. Extensive damage was caused not only to the economy of the country (Lithuania had definitely lost a potentially very important engine for its economy), but also to the image of the state, since Lithuania was eventually forced to freeze the Visaginas NPP project, which had been initiated and regionally promoted by Lithuania for more than a decade.Not everything may be considered as part of a strategy that is logical and “irresistible” for the states that strive to drop their dependency on the dominant supplier. For instance, this can be said of the EU-wide disagreements on NS2, which cause uncertainty about the EU’s unity and both its ability and willingness to fulfill its earlier commitments. Without agreeing to either stopping the construction of the Ostrovets NPP or selecting another site, Lithuania attempts to send a message to Minsk saying that such a construction is unacceptable, yet it does not receive adequate support even from its closest neighbors. The membership of the Baltic States in the IPS/UPS system could easily be used for political purposes in Russia quite soon, but the Baltic States are not very keen on speeding up any political agreement on the most favorable direction of the synchronization. There is no common long-term solution for alternative gas imports into the Baltic countries, too. Nevertheless, the latest trends are of optimistic nature: the current combination of political will and economic opportunities in the Baltic States and the EU should be a sufficient boon for reaching the set goal of the Baltic States’ integration into the Western European energy systems until 2025.
Keywords: none